TEACHER PROBLEMS IN LEARNING CHILDREN WITH SPECIAL NEEDS (ABK) AT INCLUSIVE SCHOOL SDN 1 SELONG - Risa Febriana Putri; Darmiany Darmiany; Husniati Husniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
Becoming a teacher in an inclusive school will certainly have different challenges from teaching in an ordinary school. The problems they face are more difficult than ordinary teachers. This study aims to describe the problems faced by teachers in teaching children with special needs at the inclusive school of SDN 1 Selong. This research is a case study research with a descriptive qualitative approach where the data collection methods used by the researcher are observation, interviews and documentation. The data analysis technique uses the Miles and Huberman interactive model, namely through data collection, data reduction, data presentation and drawing conclusions. The results of the study show that: not all teachers have sufficient competence in managing classes from 6 subjects, 3 of which are still not able to manage classes well, the number of students with special needs in one class, the difficulty of children with special needs receiving learning, the lack of government attention and not all parents provide support for crew members. Efforts made by teachers to overcome these problems include: the desire to continue learning to improve teacher competence, use fun methods and media, repeat learning materials, and build good communication with parents of children with special needs.